Optimization of Financial Resources Through Goal Programming - G. Srinivasaulu Goud, T. Yugandhar, Yuvaraju Macha (Mathematical Statistician and Engineering Applications, 2022)
Goal programming is used to manage a set of conflict objectives by minimizing the deviations between the target values and the realized results. The original objectives are re-formulated as a set of constraints with target values and two auxiliary variables. Two auxiliary variables are called positive deviation d+ and negative deviation d?, which represent the distance from this target value. The objective of goal programming is to minimize the deviations hierarchically so that the goals of primary importance receive first priority attention; those of second importance receive second-priority attention, and so forth. Then, the goals of first priority are minimized in the first phase. Using the obtained feasible solution result in the phrase, the goals of second priority are minimized, and so on.